Competitive systematization in age-group swimming: an evaluation of performances, maturational considerations, and international paradigms - Kojima, K.; Stager, J. M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The most appropriate method for grouping youth swimmers to assure fair competition has been debated for decades with little progress being made. The goals of this study were to evaluate the appropriateness of the age-groups at the 2nd FINA World Youth Swimming Championships and to discuss age-grouping systems used by swimming federations in the world as a means of gaining a better insight into the most appropriate age-group stratification paradigm. METHODS: All data were acquired from the official website of FINA (http://www.fina.org). The single age-grouping for each sex was composed of four CAs (ages 14-17 years for girls and ages 15-18 for boys). A relative frequency distribution of all competitors and the top 8 finishers in all 17 individual events as well as that of the relay finalists were examined for each of the four CAs. Chi-square tests, one-way ANOVA with Tukey’s post-hoc test, and Pearson product moment correlation coefficients were performed to test the research hypothesis that older swimmers within the multi-age-groups represent a greater proportion of participants and finalists. RESULTS: In girls, there were 66, 148, 218, and 322 swims by 14, 15, 16, and 17 year olds, respectively. In boys, there were 46, 152, 259, and 486 swims by 15, 16, 17, and 18 year olds, respectively. A significant difference was found between the observed and expected values in both sexes (p < 0.01). The mean relative frequencies (%) of the top 8 swimmers over 17 events were also significantly different among CAs in both sexes. The oldest CA in both sexes (age 17 for girls and age 18 for boys) had a significantly greater proportion compared with all other age categories (p < 0.05). The age-related differences were more evident in boys. DISCUSSION: Age classification systems clearly influence participation and competition outcomes in competitive youth swimming. The number of swimmers qualifying for competitive events and qualifying for finals at the Youth Championships is significantly greater for swimmers who are the oldest in their age-groups. Grouping swimmers by the use of broad CAs is not the optimal way to encourage younger competitors.